Metabolic engineering of clostridium acetobutylicum for the industrial production of 1,3-propanediol from glycerol - González-Pajuelo, María (2010)
Clostridium butyricum is to our knowledge the best natural 1,3-propanediol producer from glycerol and the only microorganism identified so far to use a coenzyme B12-independent glycerol dehydratase. However, to develop an economical process of 1,3-propanediol production, it would be necessary to improve the strain by a metabolic engineering approach. Unfortunately, no genetic tools are currently available for C. butyricum and all our efforts to develop them have been so far unsuccessful. To obtain a better ‘‘vitamin B12-free’’ biological process, we developed a metabolic engineering strategy with Clostridium acetobutylicum. The 1,3- propanediol pathway from C. butyricum was introduced on a plasmid in several mutants of C. acetobutylicum altered in product formation. The DG1(pSPD5) recombinant strain was the most efficient strain and was further characterized from a physiological and biotechnological point of view. Chemostat cultures of this strain grown on glucose alone produced only acids (acetate, butyrate and lactate) and a high level of hydrogen. In contrast, when glycerol was metabolized in chemostat culture, 1,3-propanediol became the major product, the specific rate of acid formation decreased and a very low level of hydrogen was observed. In a fed-batch culture, the DG1(pSPD5) strain was able to produce 1,3-propanediol at a higher concentration (1104mM) and productivity than the natural producer C. butyricum VPI 3266. Furthermore, this strain was also successfully used for very long term continuous production of 1,3-propanediol at high volumetric productivity (3 g L⁻¹ h⁻¹) and titer (788 mM).